Prevalence and Pattern of Ocular Symptoms in Patients with Type 2 Diabetes Mellitus Attending a Tertiary Care Hospital: A Cross-Sectional Study - Anwar. Ul Haq, Rehan Moinuddin Shaikh, Muhammad Rizwan, Aimal Khan, Chaudhry Muhammad Tariq Munawar, Mohammad Aamir Khan (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Type 2 diabetes mellitus often leads to ocular complications causing vision loss if not detected early; data on patient-reported ocular symptoms in Pakistan are limited. Objectives: To determine the prevalence and pattern of self-reported ocular symptoms among adults with T2DM and assess associations with diabetes duration, glycemic control, and retinopathy severity. Methods: From January 2022 to January 2023, eighty adults (mean age 54.9 ± 9.6 years; 57.5 percent female) with T2DM ≥ 6 months’ duration were enrolled at Sharif Medical City Hospital, Lahore, and Jinnah International Hospital, Abbottabad. Exclusion criteria comprised recent ocular surgery, non-diabetic ocular disease, active infection, or cognitive impairment. Participants completed a questionnaire on nine ocular symptoms over six months; “often” or “always” and “occasionally” if bothersome were counted as positive. All underwent slit-lamp and dilated fundus examination with ETDRS grading. HbA1c and diabetes duration were recorded. Results: Mean diabetes duration was 8.1 ± 4.9 years; mean HbA1c was 8.8 ± 1.6 percent. Diabetic retinopathy was present in 51.3 percent (mild NPDR 36.3 percent; moderate NPDR 10.0 percent; severe NPDR 5.0 percent; PDR 3.8 percent); macular edema occurred in 7.5 percent. Overall, 75.0 percent reported ≥ 1 symptom, most commonly blurred vision (60.0 percent) and dryness (35.0 percent). Symptom frequency increased with longer duration (< 5 years: 62.1 percent; ≥ 10 years: 87.5 percent; p = 0.043) and poorer control (HbA1c < 7.0 percent: 46.2 percent; ≥ 9.0 percent: 84.4 percent; p = 0.008). Multivariable analysis showed duration ≥ 10 years (AOR 2.46; 95 percent CI 1.01–5.99; p = 0.048) and HbA1c ≥ 9.0 percent (AOR 2.12; 95 percent CI 1.02–4.41; p = 0.044) as independent predictors. Conclusion: A proportion of T2DM patients report ocular symptoms correlated with longer diabetes duration and glycemic control. Incorporating symptom assessment may prompt timely referral and prevent vision-threatening complications. Keywords: Type 2 diabetes mellitus, ocular symptoms, diabetic retinopathy, prevalence, cross‐sectional study, Pakistan